2006
DOI: 10.1115/1.2720451
|View full text |Cite
|
Sign up to set email alerts
|

Flow Downstream of a Cluster of Nine Jets

Abstract: This work is an experimental investigation of the flow downstream of a low emission nozzle. The nozzle is a 3×3 square matrix of nine small swirling air jets, has a design swirl number of 0.8, and operates at a Reynolds number of 40,000. Particle image velocimetry (PIV) was used to map the velocity field under nonburning and atmospheric conditions for the first 18 jet diameters downstream of the nozzle exit plane. Seeding was liquid injected into the air stream and drops were sized to filter out those larger t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Starch granules of 5 lm mean diameter and density of 2.5 · 10 À4 g/mm 3 were used as tracer particles, which had good tracking ability and reflective performance 13,16 for the flow conditions investigated. The seeding density was set so that a The laser pulse energy was approximately 650 MJ.…”
Section: Piv Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Starch granules of 5 lm mean diameter and density of 2.5 · 10 À4 g/mm 3 were used as tracer particles, which had good tracking ability and reflective performance 13,16 for the flow conditions investigated. The seeding density was set so that a The laser pulse energy was approximately 650 MJ.…”
Section: Piv Systemmentioning
confidence: 99%
“…Boutazakhti et al 16 utilized PIV and phase Doppler particle anemometry (PDPA) to map the velocity field downstream of a 3 · 3 square matrix of nine small swirlers, in addition to a single swirler configuration. The experimental results showed that in the merger region close to the swirlers, the characteristics of individual jets were still visible and the expansion rate of the central jet was slowed.…”
Section: Introductionmentioning
confidence: 99%
“…experimental data for a cluster of nine swirling jets was recently obtained [Boutazakhti et al, 2007], while data for circular, elliptic, square, rectangular, equilateral triangular, and isosceles triangular jets was measured recently [Singh, Sundararajan, Bhaskaran, 2003].…”
Section: Swirling Jetmentioning
confidence: 99%
“…Further analysis on multiple jets has been conducted within research related to combustion or chemical mixing in Tatsumi et al (2010) and Boutazakhti et al (2007) and for ventilation supply devices by Meslem et al (2010). The study by Meslem et al (2010) showed that for an array of round jets the entrainment rate was higher close to the inlet and reducing in the downstream direction, contrary to twin round jets.…”
Section: 3mentioning
confidence: 99%